CITA HUKUM DAN SISTEM NILAI ETIKA ADVOKAT DALAM PENYELESAIAN SENGKETA HUKUM KELUARGA ISLAM - Jefry Tarantang (El-Mashlahah, 2019)
The purpose of the advocacy process in resolving Islamic family law disputes is to bring about justice, so that it requires treatment and advocacy in accordance with Islamic teachings that originate from the Koran and hadith by promoting commendable morals. This condition is a legal ideal (rechtsidee) and an ethical value system for advocates in resolving Muslim family law disputes. This research is a normative legal research with a statue approach, a conceptual approach and a philosophical/ushul fiqh approach (philosophy of Islamic law approach) then analyzed qualitatively. The ideals of the law and the ethical value system of advocates in the resolution of Islamic family law disputes are not limited to justice in positive law but also explore broader values and principles beyond positive law. These values and principles can be found through legal foundations and principles, namely the foundation of the Koran and Hadith, the basis of laws and regulations consisting of Pancasila and the 1945 Constitution, Law Number 18 of 2003 Concerning Advocates, and the Indonesian Advocate Code of Ethics for the Year 2002, philosophical foundation, theoretical foundation, juridical foundation, and sociological foundation which become advocate ethical values system through values, norms, and morals that have concepts and are interrelated and complement each other in the advocate ethics system through basic values then are translated into instrumental and concrete values be a praxis value in resolving Islamic family law disputes.